Analyze Fact Checking of Haram Sinovac Vaccine Hoax on Twitter Social Media Status - Muh. Syaiful; Muh. Akbar; Tuti Bahfiarti (Universitas Sebelas Maret, 2021)
This research discussed about haram Sinovac vaccine hoax on twitter social media status. There was something unique on Twitter social media which is trending topic system, one of the trending issue was Covid-19 vaccine that arrived from China (Sinovac) and got a lot rejection. This study aimed to determine about the fact of haram Sinovac vaccine. The research used fact checking method. Masyarakat Anti Fitnah Indonesia (MAFINDO) had standar operating procedure in checking the fact with the data collection from status in media social Twitter, on last six months (August 2020 - January 2021). This research indicated six tweets which stated that sinovac vaccine were haram and also fifteen tweets stated that sinovac vaccine are pure and halal based on the fact research. By analyze this checking fact, we can distinguish which information are hoax and fact.